AB0047 Cd55 Red-Cell Expression in Systemic Autoimmune Disease Reflects Its Impact on Erythropoiesis through Immune-Mediated Bone Marrow Insufficiency. (10th June 2014) - Asimakopoulos, J.V.; Terpos, E.; Giakoumis, A.; Kampouropoulou, O.; Papageorgiou, L.; Petevi, K.; Vaiopoulos, G.; Vassilakopoulos, T.P.; Angelopoulou, M.K.; Konstantopoulos, K.; Meletis, J.
Abstract : Background: Being fairly frequent in systemic autoimmune disease (SAD), haematological manifestations may sometimes indicate clinical exacerbation. As inflammation occurs in systemic context, haemocytopenias may occur due to bone marrow (BM) failure or excessive peripheral blood cells' (PBCs) destruction, both of which may be immune-mediated, without ignoring the drug-induced toxicity. In SAD setting, complement system overactivation can be proved detrimental to autologous tissues. Though, the role of complement regulatory proteins, such as CD55 (DAF) and CD59 (MIRL), has been poorly clarified. Their deficiency was initially described in paroxysmal nocturnal haemoglobinuria (PNH), a rare acquired non-malignant clonal haematopoietic stem cell disorder characterized by a somatic mutation of X-linked gene PIG-A, essential for glycosyl-phosphatidyl inositol anchor biosynthesis. According to the "dual pathogenesis" model, an immunoregulatory selection in favor of PNH clones to dominate over normal haemopoiesis, on a hypoplastic BM microenvironment, is equally fundamental to the pathophysiology of the disease. Its cardinal triad of chronic haemolytic anaemia, thromboembolic tendency and BM failure makes PNH a truly unique clinical syndrome. Besides, the presence of PNH clones in other haematological disorders, like aplastic anaemia or some types of myelodysplastic syndromes, has been associated with good response to immunosuppressive treatment. Objectives: The aim of this study was to assess the CD55 and/or CD59 red-cell deficiency in SAD patients and investigate their possible correlation with clinical features, laboratory parameters and undergoing treatment. Methods: CD55 and CD59 red-cell deficiency was evaluated in 86 SAD patients, 50 healthy individuals (HIN) and 7 PNH patients, using the sephacryl gel microtyping system. In all samples with "PNH-like" red blood cells (RBCs), Ham and sucrose tests were also performed. Results: Although the great majority of SAD patients (80/86, 93%) demonstrated CD55 and/or CD59 red-cell deficiency, no clinical or laboratory sign of haemolysis was observed. Interestingly, "PNH-like" RBCs never surpassed 25% of the total red-cell population in these patients. Moreover, a significant difference (δ) was revealed between the occurrence of CD55 (75/86, 87%) and CD59 (40/86, 47%) deficient red-cell populations ( δ =40%, p <0.0001). Only 3 (6%) HIN had "PNH-like" RBCs, which never exceeded 10% of the total population. All PNH patients (7/7, 100%) exhibited concomitant CD55/CD59 red-cell deficiency. Ham and sucrose tests were positive only in the latter. Conclusions: While the presence of CD55- and/or CD59- deficient RBCs was not associated with any cytopenia or specific treatment, CD55 red-cell expression was proved as a significant influence factor of haemoglobin (Hb) levels in SAD patients ( F =10.615, p =0.002). Indeed, CD55 red-cell deficiency was associated with a mean Hb reduction of 2.25 g/dl compared to its normal expression ( 95% CI: 0.88 g/dl to 3.63 g/dl, p =0.0016), reflecting the contribution of autoimmunity on impaired erythropoiesis in SAD patients, through immune-mediated BM failure. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1298